Multivariate modeling to assess user satisfaction in university libraries - Llacsa-Puma, Lidia Janeth; Tostado-Ramírez, Manuel Iván; Peña-Vélez, Isaura Vanessa; Sabando-García, Ángel Ramón (Revista de Ciencias Sociales, 2025)
University libraries face challenges in the digital age to meet the evolving expectations of users. Although there are studies on user satisfaction, few have applied a multivariate model to examine how various variables interact to affect this satisfaction. The purpose of the study was to evaluate the level of user satisfaction at the Pontificia Universidad Católica del Ecuador, using a multivariate model. A quantitative, correlational, comparative approach with a cross-sectional design was employed. The sample included 365 individuals, among students and professionals. A measurement instrument, reviewed by experts, was used and the application was conducted virtually. Analyses were carried out using SPSS and AMOS, applying reliability analysis, principal components, and structural equations. The results showed high satisfaction coefficients in all the evaluated dimensions, highlighting the importance of specialized staff, up-to-date bibliographic resources, adequate infrastructure, and a robust computer system in the perception of service. It is concluded that the multivariate model was effective in assessing and improving user satisfaction, highlighting that the library services offered by the university are considered excellent by both students and teachers and defining key areas for future interventions.